Expanding Nature’s storytelling: extended reality and debiasing strategies for an eco-agency - Reis, Cristina M.; Câmara, António (Frontiers in Psychology, 2023)
Communication in sustainability and environmental sciences is primed to be substantially changed with extended reality technology, as the emergent Metaverse gives momentum to building an urgent pro-environmental mindset. Our work focuses on immersive econarratives, supported by virtual and augmented realities, and their potential to favor an improved relationship with the environment. Considering social aggregation dynamics and cognitive bias, this article intends to 1) make the case for a new environmental narrative; 2) position extended reality as privileged settings to sustain this narrative; 3) suggest that this storytelling should be informed by Nature’s empirical evidence, i.e., ecosystem data. We see this as a chance to think this Metaverse with an embedded environmental consciousness, informed by behavior-change research.